Socialno delo v socialističnih tovarnah - Vodopivec, Nina (Družboslovne razprave, 2022)
The article deals with the development of social work in socialist textile factories in Slovenia from the 1960s. The article is based on reports of workers’ council meetings in the Pletenina knitwear factory and on research conducted by students of the School of Social Work in socialist factories, and on interviews with some former social workers in textile factories. The empirical material points to social problems identified by the social workers and the miserable social conditions in which the textile workers lived and worked. The studies conducted by the students are important sources for researching the social conditions of textile workers in the socialist past. They also point to the social understanding of the problems and social work in the former political system. I interpret the material in the context of my year-long study of the experiences of women textile workers in Slovenia
Keywords: 20. stoletje; Ljubljana; Socializem; socialna politika; Socialna služba; socialno delo; socialno skrbstvo; tekstilne delavke; Tovarne